2010
DOI: 10.1007/bf03326180
|View full text |Cite
|
Sign up to set email alerts
|

Noise pollution and its effects on medical care workers and patients in hospitals

Abstract: A BS T RA C T:The objectives of this study are to investigate the levels of noise pollution in some hospitals in Taiwan and to study the effects of noise pollution on the physiological and psychological reactions and annoyance response of medical care staff, patients and visitors in these hospitals. An instrument for the measurement of sound level was used and a self-answered survey questionnaire on noise pollution was administered. Results showed that the daily average sound levels measured inside these hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 25 publications
2
43
0
4
Order By: Relevance
“…12,13 In an other study conducted by Lawson et al, it was stated that 56% of the noise source was alarms resulting from the devices at the ICU. 3 In another study, medical devices were indicated as a source of noise, especially ventilation system, bedside infusion pumps and monitor were reported noise sources.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 In an other study conducted by Lawson et al, it was stated that 56% of the noise source was alarms resulting from the devices at the ICU. 3 In another study, medical devices were indicated as a source of noise, especially ventilation system, bedside infusion pumps and monitor were reported noise sources.…”
Section: Discussionmentioning
confidence: 98%
“…The results of many local and international studies have reported that noise inside some hospitals was more than standard. The source of this noise may be visitors or patient's family members, medical and nursing staff, rolling of trolley wheels, children playing, doors opening or closing, patients moaning or crying, renovation of hospitals, and people's footsteps (43). Bayo et al found that most of the noise in one major hospital in Spain was from sources located primarily inside the hospital (44).…”
Section: Discussionmentioning
confidence: 99%
“…Noise pollution exists in hospitals all over the world, is a common stressor and is recognized as not just as a nuisance but a serious health hazard. Various studies have measured hospital noise and linked to negative patients' quality care (Juang et al, 2010;Pope, 2010;Moshi et al, 2011). Evidence has also been accumulated that noise is a risk factor in sleep disturbance (Gabor et al, 2003;Xie et al, 2009), cardiovascular dysfunction, speech interference and mental health distortion, including hearing impairment and balance disorder (Satterfield, 2001;Ising and Kruppa, 2004).…”
Section: Introductionmentioning
confidence: 99%